Life satisfaction and its relationship with self-esteem among Najran University students - Zawahreh, Najeh Mohammad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identifying the degree of life satisfaction, the level of self-esteem and the relationship between them among students of Najran University in KSA the study sample consisted of (639) students, of whom (319) were male and (320) female students. The researcher use previous literature to building two measures, the life satisfaction scale and the self-esteem scale. Validity and reliability of both tools were concluded. the results revealed that the degree of life satisfaction among Najran University students was high, and their level of self-esteem was high, and the results showed a strong, positive and significant correlation between the degree of satisfaction with Life and the level of self-esteem, and indicated that there were no differences in life satisfaction and self-esteem among Najran University students due to the gender variable, or type of college variable.The study recommended measuring students’ life satisfaction and self-esteem periodically.